The Menopausal Symptoms of Paramedics at a Tertiary Care Center - Kumaat, Toar A; Loho, Maria F T; Suparman, Eddy (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To assess paramedic menopausal symptoms on theinpatient unit and outpatient unit.Methods: This was a cross sectional study. Data collect by fill thequestioner, the questioner fill by menopausal paramedic on Prof. Dr.R. D. Kandou Manado Hospital from October 2016 to January 2017.Data were analyzed using SPSS 22.0 for Windows.Results: Of 60 paramedics, 30 were divided to inpatient unit andthe other 30 were divided to outpatient unit. By the menopauserating scale, somatic and urogenital complaint in statistical testhave no significant differences. Psychology complaint with a moderatecomplaints on inpatient unit have 19 paramedic (63%) and12 paramedic (40%) on outpatient paramedic, in statistical havea significant differences (x2=9.62, p=0.022). On the total scoremenopausal complaints, the moderate complaints 18 paramedic(60%) on the inpatient unit and the minor complaints 21 paramedic(70%) on the outpatient unit, in statistical have a significantdifferences (x2=6.97, p=0.031).Conclusion: There is no significant difference in somatic andurogenital complaints on paramedic inpatient unit and outpatientunit. There is a significant difference in psychological complaintsand total score menopausal complaints on paramedic inpatientunit and outpatient unit.[Indones J Obstet Gynecol 2017; 5-4: 208-212]Keywords: menopause, menopause rating scale, paramedic